Electronic nose based wireless sensor network for soil monitoring in precision farming system - Ugyen Dorji (2018)
© 2017 IEEE. Notwithstandingly, soil nutrients testing methodologies are still a concern as most of them are time consuming and require laborious sampling which is expensive. In this work, electronic nose (e-nose) based wireless sensor network is designed particularly to solve this issue. Soil sensing stations installed in a precision agriculture farm can generate real time soil data online to keep track of soil status based on volatile organic compounds (VOCs). Portable e-nose was also deployed for discrimination of soil VOCs formerly treated with organic fertilizer and NPK compound fertilizers. Principal component analysis (PCA) has successfully classified VOCs indicating different level of soil fertility based on soil organic matter (SOM). VOCs pattern obtained from our e-nose is in accordance with the laboratory soil test report on total organic matter thus confirming the potential of e-nose technology to identify the soil VOCs fingerprint that will be useful for soil nutrient management in precision agriculture.